2014
DOI: 10.1002/chem.201304631
|View full text |Cite
|
Sign up to set email alerts
|

Iron Dicarbonyl Complexes Featuring Bipyridine‐Based PNN Pincer Ligands with Short Interpyridine CC Bond Lengths: Innocent or Non‐Innocent Ligand?

Abstract: A series of iron dicarbonyl complexes with bipyridine-based PNN pincer ligands were synthesized and characterized by multinuclear NMR spectroscopy ((1) H, (13) C, (15) N, (31) P), IR spectroscopy, cyclic voltammetry, (57) Fe Mössbauer spectroscopy, XPS spectroscopy, and single-crystal X-ray diffraction. The complexes with the general formula [(R-PNN)Fe(CO)2 ] (5: R-PNN=tBu-PNN=6-[(di-tert-butylphosphino)methyl]-2,2'-bipyridine, 6: R-PNN=iPr-PNN=6-[(diisopropylphosphino)methyl]-2,2'-bipyridine, and 7: R-PNN=Ph-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 116 publications
4
46
1
Order By: Relevance
“…Related mono(bipyridylmethyl)diphenylphosphines were also obtained by salt metathesis from ClPR 2 and the respective lithiated methylbipyridine as shown by Milstein et al . In our hands, reactions of LiCH 2 (bipy) (bipy=6′‐2,2′‐bipyridyl) and Cl 2 PPh in THF or Et 2 O at low temperature were not successful.…”
Section: Resultsmentioning
confidence: 61%
“…Related mono(bipyridylmethyl)diphenylphosphines were also obtained by salt metathesis from ClPR 2 and the respective lithiated methylbipyridine as shown by Milstein et al . In our hands, reactions of LiCH 2 (bipy) (bipy=6′‐2,2′‐bipyridyl) and Cl 2 PPh in THF or Et 2 O at low temperature were not successful.…”
Section: Resultsmentioning
confidence: 61%
“…However, ligand/metal charges are a continuum phenomenon, and the assignment of redoxnon-innocent behavior versus ligand p-donor/acceptor behavior is often not clear. [13] Recently, the Neidig and Milstein groups demonstrated that even seemingly definitive bond length perturbations can be misleading.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] For example, Milstein and coworkers demonstrated the role of PCP and PNP pincer ligands in catalysis and small molecule activation and proposed mechanisms in which metal-ligand cooperation plays a major role (Chart 1c). [13][14][15][16][17][18][19][20][21] In addition, Chirik and coworkers exploited the potential of base metals in catalytic transformations by using flexible and redox non-innocent ligands to overcome the limitation of first row transition metals that usually undergo single electron processes (Chart 1d). [22][23][24][25] Besides traditional phosphine and nitrogen donors, an arene is suitable for metal-ligand cooperation as well: first, the coordination mode of the arene can vary from  6 to  2 according to the degree of delocalization.…”
Section: Introductionmentioning
confidence: 99%